Early identification and intervention of autism spectrum disorder among young children - Badzis, Mastura; Zaini, Mimi Fitriana (IIUM Press, 2014)

(untitled)
The present study focused on the paramount importance of early identification and intervention of Autism Spectrum Disorder (ASD) among young children. The focus of the study is on children with autism and their typical characters which are identified by adults. The study investigates the occurrence of Autistic Spectrum Disorder (ASD) among young children from the parents’ perspective. This descriptive and analytical study aimed at finding 1) parents’ perception of the need of early identification and intervention of children with autism, 2) parents’ own perception of the challenges and strategies to help students with autism increase their school performance and 3) parents’ view on strategies to help change the societal perception on ASD. There were three research questions to investigate the parents’ perception in the current study; 1) the issue pertaining to the need of early identification of children with autism, 2) the questions related to useful of identification to parents, school teachers and society, 3) the questions on the challenges and strategies parents had to help ASD children receive optimal care by adults. It was found that parents identified their children behavior as ASD, regardless its degree of severity. The behaviors such as 1) emotionally unstable with bad tempered, 2) easy to be frustrated, 3) having ritual behavior, 4) quick walking habit, 5) problem with understanding, 6) reserved personality and lonely were identified with the help of the teachers in school. Strategies to help children with autism are also discussed in this paper.